Analysis of Student Learning Motivation on The Basis of Providing Guidance and Counseling Services to Higher Education - Hartini, Hartini (International Research-Based Education Journal, 2023)
This study aims to analyze student interest in learning so that data can be used as a basis for providing guidance and counseling services in tertiary institutions. The research method uses a quantitative approach. The subjects of this study were 46 students. The research instrument is a questionnaire. Data analysis using percentage technique. The results showed that students' interest in participating in the learning process was in the very high category 17.39%, high 26.29%, medium 21.74%, low 23.91% and very low 10.78. Guidance and counseling services designed for students who have motivation in the very good, good and sufficient category can be provided with online information sharing services via the website to all students as a function of prevention, development and maintenance. Whereas in the low and very low categories, responsive services are provided to category students through individual counseling and group counseling. As a function of tightening the problems encountered